Specialist geriatric medical assessment for patients discharged from hospital acute assessment units: randomised controlled trial - Edmans, Julie; Bradshaw, Lucy; Franklin, Matthew; Gladman, John R.F.; Conroy, Simon (British Medical Association, 2013)
Objective To evaluate the effect of specialist geriatric medical management on the outcomes of at risk older people discharged from acute medical assessment units.